Decarbonisation of operations management – looking back, moving forward: a review and implications for the production research community - de Sousa Jabbour, Ana Beatriz Lopes; Chiappetta Jabbour, Charbel Jose; Sarkis, Joseph; Gunasekaran, Angappa; Furlan Matos Alves, Marcelo Wilson; Ribeiro, Daniela Andriani (Taylor & Francis, 2018)
This paper systematically analyses the vital motivations, drivers and barriers to the adoption of low-carbon operations management practices in response to climate change, highlighting the implications for the International Journal of Production Research (IJPR)’s community, which has contributed significantly to discussion of and research into sustainable production. Based on a thorough review of key articles on low-carbon operations management published in a number of prestigious journals, seven propositions for future research are suggested. Additionally, a unique classification of the barriers to and motivations for low-carbon production is put forward. These areas, which deserve further investigation, are (a) economic issues, (b)  policy, (c) technology, (d) governance and (e) the market. The research agenda proposed for low-carbon production and operations may prove useful to the production research community in planning future developments and research projects, increasing knowledge and designing teaching modules on the topic. The study concludes by shedding light on the main research opportunities that IJPR’s community will encounter.
Keywords: climate change; low-carbon economy; sustainable industrial engineering; sustainable operations management; sustainable production; sustainable supply chain